Arthroscopic Treatment of Translunate Perilunate Injuries, Not Dislocated (PLIND) - Herzberg, Guillaume; Cievet-Bonfils, Maxime; Burnier, Marion (Journal of Wrist Surgery, 2019)
Background Translunate perilunate dislocations were recently described as well as perilunate injuries, not dislocated (PLIND). The authors present a case of transradial styloid, translunate PLIND which sustained a full arthroscopic reduction and internal fixation.Case Description A 33-year-old man sustained a transradial styloid, translunate PLIND due to a fall from a truck with his wrist in hyperextension. The diagnosis was made at the acute stage. Full arthroscopic reduction and internal fixation with Kirschner wires was performed, followed by a 6 weeks' immobilization period. Uneventful healing of both the lunate and radial styloid were observed at 6 weeks and confirmed with a computed tomography scan. At 4 years of follow-up, the Lyon wrist score was 78% (good).Literature Review Very few lunate fractures are described in the literature. Translunate perilunate dislocations were recently described as well as PLIND. To the best of the authors' knowledge, a case of transradial styloid, translunate PLIND which sustained a full arthroscopic reduction and internal fixation has never been reported so far.Clinical Relevance This case reports a unique pattern of transradial styloid, translunate PLIND and outlines the usefulness of a full arthroscopic treatment. An open reduction for this pattern of injury would have been extensive, difficult, and probably unreliable.
Keywords: perilunate injuries; not dislocated; lunate fracture; perilunate dislocations; wrist arthroscopy